Philological and historical commentary on Ammianus Marcellinus XXX - Boeft, J. den.; Drijvers, Jan Willem.; Hengst, Daniël den.; Teitler, H. C. (Philological and Historical Commentary on Ammianus Marcellinus, 2015)
The first part of Book 30 of Ammianus Marcellinus' Res Gestae is devoted to the military and diplomatic struggle for Armenia between Valens, emperor of the East, and king Sapor II of Persia. The Romans successfully defend their position, until they are forced to deal with the Goths who threaten to cross the Danube border. The second half of Book 30 is dominated by Valentinian I, emperor of the West. Ammianus presents a kaleidoscopic picture of this emperor alternating between admiration for his military qualities and devotion to his duty and bitter criticism of his avarice and cruelty. The account of his death forms the conclusion of Ammianus' treatment of the history of the western half of the Empire.